Kontribusi Pemikiran Ekonomi Islam dalam Sejarah Ekonomi Dunia - Syarifah; Zuhriadi, M.; Amanda, Dhea; Purba, Bonaraja (As-Syirkah: Islamic Economic & Financial Journal, 2024)
In this research, we explore Islamic economics in world economic history. The main focus of this research is analyzing how the principles of Islamic economics have contributed and played a role in shaping global economic development. Through literature studies starting from basic concepts of Islamic economic thought such as sharia, zakat, to financial principles in Islamic teachings, the development of Islamic economics. The results of this research pay attention to the positive impact of Islamic economics in forming a just economic system. Islamic economic thought is identified as a major player in forming an economic paradigm that emphasizes social responsibility, equitable distribution of wealth, and environmental sustainability.